Using bidirectional chemical exchange for improved hyperpolarized [13C]bicarbonate pH imaging. Issue 3 (3rd May 2019) - Korenchan, David E.; Gordon, Jeremy W.; Subramaniam, Sukumar; Sriram, Renuka; Baligand, Celine; VanCriekinge, Mark; Bok, Robert; Vigneron, Daniel B.; Wilson, David M.; Larson, Peder E.Z.; Kurhanewicz, John; Flavell, Robert R.
Abstract : Purpose: Rapid chemical exchange can affect SNR and pH measurement accuracy for hyperpolarized pH imaging with [ 13 C]bicarbonate. The purpose of this work was to investigate chemical exchange effects on hyperpolarized imaging sequences to identify optimal sequence parameters for high SNR and pH accuracy. Methods: Simulations were performed under varying rates of bicarbonate–CO2 chemical exchange to analyze exchange effects on pH quantification accuracy and SNR under different sampling schemes. Four pulse sequences, including 1 new technique, a multiple‐excitation 2D EPI (multi‐EPI) sequence, were compared in phantoms using hyperpolarized [ 13 C]bicarbonate, varying parameters such as tip angles, repetition time, order of metabolite excitation, and refocusing pulse design. In vivo hyperpolarized bicarbonate–CO2 exchange measurements were made in transgenic murine prostate tumors to select in vivo imaging parameters. Results: Modeling of bicarbonate–CO2 exchange identified a multiple‐excitation scheme for increasing CO2 SNR by up to a factor of 2.7. When implemented in phantom imaging experiments, these sampling schemes were confirmed to yield high pH accuracy and SNR gains. Based on measured bicarbonate–CO2 exchange in vivo, a 47% CO2 SNR gain is predicted. Conclusion: The novel multi‐EPI pulse sequence can boost CO2 imaging signal in hyperpolarized 13 C bicarbonate imaging while introducing minimal pH bias, helping to surmount a major hurdle in hyperpolarized pH imaging.